Cassette for the Generation of Sequential Gene Disruptions in the Yeast Schizosaccharomyces pombe. (June 1997) - McNabb, David S.; Pak, Sally M.; Guarente, Leonard
The ability to conveniently construct gene disruptions is an important methodology for genetic analysis of the fission yeast Schizosaccharomyces pombe . Because of the limited number of selectable markers available for generating gene disruptions in fission yeast, the construction of strains that contain multiple gene disruptions can be quite difficult. This becomes a particular problem when episomal plasmids carrying selectable markers are also required within the same strains. To alleviate these difficulties, we have constructed a hisG-ura4 + -hisG cassette that can be used repeatedly for constructing gene disruptions in S. pombe . This cassette allows the recycling of the ura4 + marker, thereby permitting the disruption of an indefinite number of genes sequentially within the same strain and/or for subsequently introducing a ura4 + -marked plasmid.